Partilha do trabalho: efeitos na jornada real e nos sal??rios - CAVALCANTI, Andr?? Luiz Cordeiro (2003)
This Master thesis deals with the effects of sharing work in generating new jobs. Job Sharing is a reduction in working hours determined in legislation, and is also known as work-sharing. The argument that the division of labor increases the supply of jobs in the economy has been investigated in several countries, reaching the conclusion that the effect of this measure is ambiguous, and that would only result if there were effective measures desonerasem the fixed costs of hiring new employees, otherwise, firms tend to demand overtime for employees already employed, instead of making new hires, given that these two factors are substitutes, and the marginal cost of hours is not affected by the reduction in journey work, while the marginal cost of a new engagement increases with this measure. Thus, following the model that Jennifer Hunt (1996) used in Germany, was made an empirical study for the Brazilian case, examining the effects of a reduction in legal working day in day actually worked and wages, using data from National Household Survey for the years 1982 to 2001. It turned out that the behavior of these two variables follow the results found by Hunt (1996), and that work sharing is not an effective way to generate jobs.